Pelatihan Paralegal dan Konselor Bagi Perempuan Lintas Etnis, Suku dan Mahasiswa di Kabupaten Jember - ., Supianto (Al-Khidmah Jurnal Pengabdian Masyarakat, 2024)
Access to justice and legal certainty for victims of violence against women, especially violence in the domestic sphere, must receive attention. In Jember Regency, the rate of violence against women is still quite high and various efforts are needed to prevent and reduce the occurrence of new violence. One effort to reduce and prevent violence against women is to provide training for paralegals and counselors who are expected to be able to provide advocacy to victims and provide education to the general public. The training method used is a presentation followed by discussion to answer various problems faced by the participants. Overall, it can be concluded that paralegal and counselor training activities for women across ethnicities, tribes and students are running smoothly without significant obstacles. However, training activities are still considered inadequate if they are only carried out once, this is because cases that occur in society experience the development of different forms and modus operandi so that paralegals and counselors need partners to share new experiences and knowledge. Therefore, further training is needed.